2013
DOI: 10.1134/s1063783413030244
|View full text |Cite
|
Sign up to set email alerts
|

Sizes and fluorescence of cadmium sulfide quantum dots

Abstract: Abstract-Cadmium sulfide quantum dots have been synthesized by wet chemical deposition from an aque ous solution. The sizes of the quantum dots determined by dynamic light scattering directly in the colloidal solution and by intermittent contact atomic force microscopy in the dry sediment agree with each other. It has been found that splitting of the fluorescence peaks of the quantum dots can be affected by the disorder of the atomic structure of cadmium sulfide quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The commonly accepted boundary of stability of a colloidal solution is the value of the zeta potential of ±30 mV. In the sam ples under study, this value varied from 0 to -50 mV with the maximum at -24 mV, which indicates a suffi cient stability of the solution but does not exclude the formation of a small amount of larger particles [12].…”
Section: Sample Preparation Experimentalmentioning
confidence: 99%
“…The commonly accepted boundary of stability of a colloidal solution is the value of the zeta potential of ±30 mV. In the sam ples under study, this value varied from 0 to -50 mV with the maximum at -24 mV, which indicates a suffi cient stability of the solution but does not exclude the formation of a small amount of larger particles [12].…”
Section: Sample Preparation Experimentalmentioning
confidence: 99%
“…It is seen that the LE band dominates in the spectrum of CTAB-coated NPs. Keeping in mind that the localized states on the surface of NPs [17][18][19] contribute to the LE band emission, one can suggest that using surfactant for covering the NP surface with the bilayer of CTAB (see Fig. 4b) drastically diminishes the non-radiative quenching of surface-related PL that is characteristic for surface/polymer interface (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…448,449 A study of the size distribution of scattering sites found by the dynamic light scattering technique demonstrated that most of the particles have the size of 15 nm. This size includes the 1 nm thick layer of the stabilizing agent (small-angle neutron scattering data) and the 5 nm thick solvation shell.…”
Section: Viii1 Selective Oxidation Of Organic Compounds By Photocatmentioning
confidence: 99%